Sifat Mekanik Beton Polimer Epoksi dengan Pengisi Partikel Nanokalsit-silika - Nugrahani Primary Putri; Diah Hari Kusumawati; Lydia Rohmawati (Sains dan Matematika, 2014)
Polymer concrete environmentally friendly by utilizing the waste has been developed, one with waste mussel shells and sidoarjomud. Utilization of the waste is not optimal, for it to be used as filler in polymer concrete waste will be expected to have a highereconomic value. This research aimed to utilize the waste of cockle's shells and sidoarjo mud as filler of polymer concrete. Both waste firstsynthesized into nano particles by taking calcite and silica alone (mussel shells into nanocalsite and sidoarjo mud into nanosilica), beforebeing used as a filler. Once formed nanocalsite and nanosilica, composites with epoxy resin matrix and filler nanocalsite and nanosilicacreated by varying the percentage weight of each filler 5-10% by weight. Then the characterization was conducted in the form of tensiletest, hardness, bending and impact test. The test results showed that the resulting polymer concrete has physical properties, mechanical,thermal and microscopic good and has an optimum value at 10% filler calcite + 10% silica, which is 218.39 MPa compressive strength,tensile strength of 3.32 MPa, a strong fracture of 8.04 MPa and hardness values ranged from 16.08 to 18.3 HVN. Overall the resultshave met the standards for the characterization of polymer concrete.